2021
DOI: 10.3389/fmed.2021.699672
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing Reveals Exonic Variation of ASIC5 Gene Results in Recurrent Pregnancy Loss

Abstract: Family trio next-generation sequencing-based variant analysis was done to identify the genomic reason on unexplained recurrent pregnancy loss (RPL). A family (dead fetus and parents) from Saudi Arabia with an earlier history of three unexplained RPLs at the ninth week of pregnancy was included in the study. Whole-genome sequencing (WGS) of a dead fetus and the parents was done to identify the pathogenic variation and confirmed through Sanger sequencing. WGS of dead fetus identifies a novel homozygous exonic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…One of the fetal tissue reported with homozygous ASIC5 Saudi mutation. 27 As the fetal tissue samples were collected from aborted 9-week fetuses therefore clinical confirmation of the gender of the fetus could not be achieved. Early prenatal diagnosis of gender and identification of disease associated mutations can provide effective decision making in the mother among high-consanguinity population to decide within the allowed time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the fetal tissue reported with homozygous ASIC5 Saudi mutation. 27 As the fetal tissue samples were collected from aborted 9-week fetuses therefore clinical confirmation of the gender of the fetus could not be achieved. Early prenatal diagnosis of gender and identification of disease associated mutations can provide effective decision making in the mother among high-consanguinity population to decide within the allowed time.…”
Section: Discussionmentioning
confidence: 99%
“…Early prenatal diagnosis of gender and identification of disease associated mutations can provide effective decision making in the mother among high-consanguinity population to decide within the allowed time. 27 , 28 The eight pairs of primers designed in the study is highly specific, sensitive, unique and well matched for the simultaneous detection of the male specific Y-biomarkers, SRY, DAZ2 and TSPY1 genes and the internal control, ACTB gene for both conventional PCR and real-time qPCR. The specificity of the primers were confirmed through sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic abnormalities such as chromosome abnormalities, submicroscopic chromosome deletion and duplications, and gene sequence variation are the major genetic causes of female infertility [ 22 ]. Whole-genome sequencing revealed that even single gene causes could explain infertility and pregnancy complications [ 23 ]. However, these complications are often challenging due to their multitissue and multiorganism nature.…”
Section: Factors Affecting Female Infertilitymentioning
confidence: 99%
“…Studies on systemic juvenile idiopathic arthritis (LACC1 gene) [80,81]; recurrent pregnancy loss (ASIC5 gene) [82]; tricho-hepato-enteric syndrome (SKIV2L and TTC37 genes) [83];…”
Section: Other Genetic Diseasesmentioning
confidence: 99%
“…Variants in the Mendeliome in Saudi ancestry – APC-related Cenani-Lenz syndrome, Steel syndrome, syndromic cataract, oral-facial-digital syndrome, CHARGE-like presentation, epileptic encephalopathy, Ehlers-Danlos-like syndrome, and congenital hydrocephalus – were reported either with compatible phenotypes (homozygous variant in 30 genes) or phenotypes different from the original reports (homozygous mutations in 18 candidate genes) [ 79 ]. Studies on systemic juvenile idiopathic arthritis ( LACC1 gene) [ 80 , 81 ]; recurrent pregnancy loss ( ASIC5 gene) [ 82 ]; tricho-hepato-enteric syndrome ( SKIV2L and TTC37 genes) [ 83 ]; STING-associated vasculopathy of infantile-onset ( STING1 gene) [ 84 ]; multiple congenital anomaly syndrome ( SMG9 gene) [ 85 ]; diabetic retinopathy ( NME3 , LOC728699 , and FASTK genes) [ 86 ]; congenital neutropenia with inflammatory bowel disease ( G6PC3 gene) [ 87 ]; skeletal dysplasia ( XYLT1 ) [ 88 , 89 ]; Wolf–Hirschhorn syndrome ( WHSC1 gene) [ 90 ]; lymphatic dysplasia with nonimmune hydrops fetalis ( PIEZO1 ) [ 89 ]; Cohen syndrome ( VPS13B gene) [ 91 ]; severe combined immunodeficiency disease ( AK2 , JAK3 , and MTHFD1 genes) [ 92 ]; celiac disease ( CPED1 gene) [ 93 ]; hereditary spherocytosis type 3 ( SPTA1 gene) [ 89 ]; developmental delay, cerebellar hypoplasia, and myoclonic seizures ( KCNMA1 gene) [ 74 ]; Cenani-Lenz syndrome ( APC gene) [ 74 ]; Sjogren-Larsson syndrome ( ELOVL4 gene) [ 74 ]; autism spectrum disorder (multigene) [ 94 ]; congenital heart disease ( PRKD1 gene) [ 95 ]; ciliopathies [ 96 ]; Parkinsonism ( PLA2G6 gene) [ 97 ]; retinal dystrophies ( CLRN1 , ABCA4 , CERKL , AGBL5 , CDH16 , and DNAJC17 genes) [ 98 100 ]; pediatric asthma [ 101 ]; cardiovascular genetic diseases ( LDLR gene) [ 102 ]; enteroendocrine dysfunction ( PCSK1 ) [ 103 ]; tricho-hepato-enteric syndrome ( TTC37 and SKIV2L ) [ 104 ]; Wolcott–Rallison syndrome ( EIF2AK3 ) [ 105 ], Fanconi–Bickel syndrome ( SLC2A2 ) [ ...…”
Section: Other Genetic Diseasesmentioning
confidence: 99%